ハンティ語の音声音韻の特徴について : 言語フィールド調査データからのまとめ - 松本, 亮; 1446 (神戸山手大学, 2019)
40022182041 In my very first linguistic field research for Khanty language in Salekhard, Yamalo-Nenets Autonomous Okrug, Russia, which belongs to the Ugric languages of Uralic languages family, 100 basic words have been recorded. In this research note I attempted to construct the phonemic inventory and to indicate some problems of Khanty language, the Shuryshkar dialect. Finally I siuggest the aspects from which the further linguistic reseach should be done. departmental bulletin paper